Yolo - Myracle, Lauren, 1969- (Myracle, Lauren, 1969- Internet girls series., 2014)
Through "instant messages," chronicles the struggles best friends Maddie, Angela, and Zoe face during their freshman year in college, each of them in a different state, two wondering if their romantic relationships will last, and one determining that roller derby is the key to keeping the trio close.